1989
DOI: 10.1007/bf02559635
|View full text |Cite
|
Sign up to set email alerts
|

Estramustine phosphate (Estracyt®) in the treatment of prostatic carcinoma

Abstract: This review presents the most important hormonal, cytotoxic and pharmacokinetic properties of estramustine phosphate. Furthermore the results of randomized Phase III trials are described in patients with hormone refractory prostatic cancer with and without previous irradiation. Several randomized studies are reported with Estracyt also in the primary treatment of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The first hormonally targeted chemotherapeutic agents developed for the treatment of prostate cancer and breast cancer used estrogenic steroid molecules as carriers for various alkylating agents (13,14). Nitrogen mustard compounds were chemically coupled to carrier estrogens for enhancing selectivity and cytotoxicity on estrogen receptor-positive cells (13,14).…”
Section: Hormonal Chemotherapeutic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first hormonally targeted chemotherapeutic agents developed for the treatment of prostate cancer and breast cancer used estrogenic steroid molecules as carriers for various alkylating agents (13,14). Nitrogen mustard compounds were chemically coupled to carrier estrogens for enhancing selectivity and cytotoxicity on estrogen receptor-positive cells (13,14).…”
Section: Hormonal Chemotherapeutic Agentsmentioning
confidence: 99%
“…Nitrogen mustard compounds were chemically coupled to carrier estrogens for enhancing selectivity and cytotoxicity on estrogen receptor-positive cells (13,14). The cytotoxic estrogens, such as estracyte (estramustine), accumulate in the rat prostate due to the presence in the ventral lobe of the prostate of a protein that binds estramustine with high affinity and high capacity (13,14).…”
Section: Hormonal Chemotherapeutic Agentsmentioning
confidence: 99%
“…In early studies with hormone receptor targeted chemotherapy, alkylating agents were coupled to estrogenic steroid molecules [168,169]. Also daunorubicin was coupled to β-melanocyte-stimulating hormone for achieving receptor targeting [170].…”
Section: Hormone Receptorsmentioning
confidence: 99%
“…In a 1989 review of the early studies, Konyves [7] showed that, in the primary treatment of prostate cancer, the response to estramus tine was only marginally better than to castration. There does appear, however, to be an advantage in patients pre Combined Hormonal and Differentiation Therapy…”
Section: Secondary Hormone Manipulationmentioning
confidence: 99%
“…Possible strategies to prevent hormone refractoriness and for the introduction of cyto-KARGER senting initially with poorly differentiated tumours. The recent demonstration that the use of antiemetics and H, blockers before and during the therapeutic administra tion of estramustine has improved not only the sideeffect profile of the drug but also its acceptability as long-term therapy [7], However, as a second-line treat ment following castration, or other primary hormonal relapse, there does seem to be a place for this combina tion therapy in terms of its subjective though not objec tive response. In a recent review Eisenberger [8] looked at a number of studies, including 561 patients in total, and has shown that, although there is only a 5% com plete and partial response, 25% of patients had a good subjective response for at least 10 months.…”
mentioning
confidence: 99%